Comparative Analysis of Banking Financial Performance Pre and Post Covid-19 Pandemic - Pramitasari, Triska Dewi (MEC-J (Management and Economics Journal), 2021)
Covid-19 struck the Indonesian banking industry in particular ASEAN, through the weaker economic growth, which resulted in a slowdown in credit growth and eventually reduce profitability. This study aimed to analyze the financial performance of banks before and after the occurrence of a covid-19 pandemic and formulate alternative strategies to improve the financial performance of Indonesian banks. The study sample consisted of four banks with saturated sampling method (census) are owned banks (State Bank) listed on the Stock Exchange Indonesia. The data in this research is secondary data obtained from the bank's annual report period 2019 until the second quarter of 2020 which is accessed via the IDX website. Performance is measured using the six financial ratios namely ROA, BOPO, NPL, NIM, CAR and LDR with different test analysis method (Paired T-Test). The study found that in the form of financial ratios ROA, BOPO, CAR and LDR pre and post Covid-19 pandemics have significantly different values, while the NPL and NIM did not differ significantly.